Wanita Usia 32 Tahun, Hamil 34 Minggu dengan Plasenta Previa Totalis dan Janin Letak Lintang - Ilham, Arifin; Zulfadli, Zulfadli (CV. Jasa Sukses Abadi, 2025)
Complaints of vaginal bleeding since 5 hours before admission to hospital. In this case, a physical examination and supporting examination in the form of ultrasonography were carried out so that it could be concluded that the cause of vaginal bleeding was placenta previa totalis with a single live fetus in the latitude. Placenta previa is a placenta that implants in the lower segment of the uterus so that it covers all or part of the internal uterine ostium. The frequency of antepartum bleeding is around 3% to 4% of all deliveries. The incidence of placenta previa varies between 0.3-0.5% of all births. Placenta previa is the most common cause of all cases of antepartum hemorrhage. This study is a case report of a pregnant woman, 32 years old, G2P1A0 34 weeks, who came with complaints of vaginal bleeding without pain and abnormalities in the position of the fetus. During the obstetric physical examination, it was found that the results of the inspection showed vaginal bleeding, the results of the palpation showed that the fetus was in a horizontal position, the results of the inspection showed that there was flux coming out of the external uterine ostium. Supporting examinations revealed an Hb level of 8.2 g/dl. Therefore, the patient was diagnosed with placenta previa totalis and the fetus was transversely located. The management of this patient was expected to be discharged in good condition and scheduled for a cesarean section cesarean.